The Influence of Foreign Loan Lender Guidelines on the Project Consulting Services Tender in Indonesia - Setiawan, Budi (Journal of Infrastructure Policy and Management (JIPM), 2025)
This study investigates the influence of the Saudi Fund for Development (SFD) guidelines on the tender process of consultancy services in Indonesia, specifically for foreign loan-financed projects. It investigates the differences between Indonesia’s national regulations, laid out in Presidential Decrees, and lender-specific guidelines, which are mandatory when external funding is used. This qualitative research applied interviews with actors holding decision-making authority within the procurement process. The data were examined through a thematic analysis using NVivo 12 software. Two significant differences between the SFD guidelines and Indonesia’s national regulations were established. First, a manual process is stipulated by SFD guidelines, yet an electronic platform is preferred by Indonesia’s regulations, which triggers extensive delays. Second, obtaining a No Objection Letter (NOL) from a lender for every phase of the tender process is a time-consuming demand that creates bottlenecks situation and prolongs the process. The research emphasizes that critical issues arise when balancing such differing sets of regulations, which are counterproductive for a smooth and timely process. Thus, harmonized national and lender-specific regulations are needed to minimize delays and accelerate a smooth process of service procurements.